2018
DOI: 10.1055/s-0038-1649482
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sonographic Estimated Fetal Weight and the Risk of Cesarean Delivery among Nulliparous Women with Diabetes in Pregnancy

Abstract: An US-EFW within 35 days of delivery among nulliparous women with medication-requiring diabetes was positively associated with intrapartum cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The common use of US to evaluate fetal weight increased the rate of CS even among pregnancies with lower EFW. Dude et al found an increased rate of CS among women who had US EFW 5 weeks prior to delivery, even after accounting for birth weight [ 178 ]. Among 304 diabetic pregnancies, 231 had US EFW, of them, 66 (28.6%) had the pre-delivery diagnosis of LGA.…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 1 more Smart Citation
“…The common use of US to evaluate fetal weight increased the rate of CS even among pregnancies with lower EFW. Dude et al found an increased rate of CS among women who had US EFW 5 weeks prior to delivery, even after accounting for birth weight [ 178 ]. Among 304 diabetic pregnancies, 231 had US EFW, of them, 66 (28.6%) had the pre-delivery diagnosis of LGA.…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…Among the 165 women with the pre-delivery diagnosis of EFW AGA, 6 (3.6%) were LGA. Pregnancies predicted to have an LGA infant were more likely to undergo a CS with the diagnosis of an arrest disorder [ 178 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%